Internet technologies in the activities of travel agencies to organize the spare time of young people - Гадецька, Зоя Митрофанівна; Ус, Михайло Федорович (Eastern-European Journal of Enterprise Technologies, 2010)
This article discusses the problem of the opportunities the global computer network in the activities of travel agencies to organize and spend the spare time of young people, the ways of placing travel advertisement in the network.